The fundamental factors contributing to the behavior of students: An overview of psychological pedagogy - Ghafar, Zanyar Nathir (Yayasan Mitra Persada Nusantara, 2023)
The main duty of an educator is to facilitate the process of education. However, it is vital to acknowledge that teachers are involved in several activities and assume various tasks. In addition to disseminating essential information to their students, educators are also tasked with the duty of effectively managing a varied range of student characteristics and behaviors. Therefore, it is a matter of worry when educators exhibit a deficiency in the requisite abilities to adequately facilitate student learning and possess inadequate understanding in the domain of psychological pedagogy. Acquiring information and understanding of the fundamental variables that contribute to the variability in students' behavior is an essential strategy for educators to effectively provide assistance and instruction to their students. This article next highlights significant factors that contribute to the fundamental causes of pupils' behavioral patterns. Furthermore, it emphasizes the need for educators to have a thorough comprehension of the fundamental factors contributing to students' conduct, with the aim of augmenting their efficacy in the field of instruction.